Navigating Ottawa Resources To improve Health: A virtual student-clinic pilot to strengthen social medicine education - Lee, Seung Heyck; Jebanesan, Aravinth; Wang, Katelyn; Wisener, Nicole; Liang, Emily; Timm, Makenna; Kendall, Claire E; Bennett, Susan (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Implication StatementThe practice of social medicine, which requires skills in interprofessional collaboration and navigating community resources, is crucial for training students to provide holistic care. We developed a social needs-based virtual student-run clinic called Navigating Ottawa Resources To improve Health (NORTH) to assist newcomers and underserved families with navigating community resources in Ottawa, Ontario. We found that pre-clerkship medical students improved their knowledge and comfort-level with addressing social needs while clients found the service helpful for accessing community support. NORTH is an effective learning opportunity for pre-clerkship medical students to practice social medicine and serve vulnerable communities that can be organized and operated in other communities.